Case comment: the unauthorized use of the image of a football player in videogames as a violation of image rights in Brazil. Issue 2 (December 2018) - Westenberger, Paula
Abstract : This case comment analyses a decision by the São Paulo Court of Appeal in a case concerning whether the use of the image of a football player in a videogame, without the athlete's permission, constituted a violation of his image rights. The Court of Appeal found that the use of the image of a public person, without their consent, in a commercial activity with no relevant public interest to be protected, harms a fundamental personality right and generates the right to compensate for damages.